2021
DOI: 10.1002/ab.21951
|View full text |Cite
|
Sign up to set email alerts
|

Association between bullying victimization and e‐cigarette use among German students

Abstract: This study examined the association between bullying victimization and e‐cigarette use. Data from a 2019–2020 German student survey were used (N = 16,476). The target population consisted of students enrolled in grades 5–10, with a mean age of 13.1 years (SD = 1.8), and equal gender distribution (49.5% female). Mixed‐effect multivariable logistic regression models were used to examine the association between bullying victimization (attacked physically, assaulted verbally, experienced relational bullying, sexua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…Studies have related its use to adverse mental health effects like depression [ 21 ]. In accordance with our findings, another recent study from Germany indicated an empirical relationship between cyberbullying and e-cigarette use among students [ 22 ]. However, research in this field is in a nascent stage and enormous scope exists for in-depth qualitative and quantitative studies relating to the use of e-cigarettes and their impact on mental health behavior and social media use.…”
Section: Discussionsupporting
confidence: 93%
“…Studies have related its use to adverse mental health effects like depression [ 21 ]. In accordance with our findings, another recent study from Germany indicated an empirical relationship between cyberbullying and e-cigarette use among students [ 22 ]. However, research in this field is in a nascent stage and enormous scope exists for in-depth qualitative and quantitative studies relating to the use of e-cigarettes and their impact on mental health behavior and social media use.…”
Section: Discussionsupporting
confidence: 93%
“…Sexual minorities and bullying victims have been the priority populations in scholarly inquiry about youth tobacco use [54][55][56][57]. Multiple studies report a higher prevalence of e-cigarette use among sexual minorities and bullying victims [47,58,59], especially those bullied among sexual minority adolescents [60].The public health community thus needs to devote special consideration to these populations, for example, combatting the misleading marketing targeted to sexual minority youth by the tobacco industry [47].…”
Section: Theme 1: Epidemiology and Kabsmentioning
confidence: 99%
“…To date, little research has focused on the link between bullying and vaping. These studies generally find that adolescent bullying victimization is associated with vaping (Azagba et al, 2020; Boccio et al, 2022; Doxbeck, 2020; Hansen et al, 2021; Ihongbe et al, 2021; Pontes et al, 2021; Ragavan et al, 2021). For example, Azagba et al (2020) found that adolescents who were bullied daily or almost daily were likely to use e-cigarettes more frequently than adolescents who were not bullied.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Specifically, we examine the associations between lifetime and last 30 day nicotine and marijuana vaping and bullying perpetration, bullying victimization, and bully-victim status for both in-person and cyberbullying. The majority of studies that have explored connections between vaping and bullying activities have measured vaping as whether or not an adolescent has used an e-cigarette (Azagba et al, 2020;Doxbeck, 2020;Hansen et al, 2021;Ihongbe et al, 2021;Pontes et al, 2021;Ragavan et al, 2021). While important to study, general measures of vaping treat all types of vaping similarly even though research has established that differential relationships exist between the various forms of vaping (Jackson et al, 2019(Jackson et al, , 2020.…”
Section: The Current Studymentioning
confidence: 99%